2016
DOI: 10.1111/ddg.13144
|View full text |Cite
|
Sign up to set email alerts
|

Physical modalities for the treatment of rosacea

Abstract: SummaryRosacea is characterised by a wide variety of vascular changes. Apart from telangiectasia and erythema, often so-called flushing occurs. These vascular abnormalities can be targeted with specific light and laser devices. In addition to KTP laser, pulsed dye laser (PDL) and Nd:YAG laser, also intense pulsed light devices (IPLs) are used. The described therapeutic effects include the reduction of vascular abnormalities and even improvement of papulopustular changes. While the KTP laser shows very good res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 35 publications
(53 reference statements)
1
26
1
1
Order By: Relevance
“…KTP laser has also been reported to be very safe when used in combination with topical retinaldehyde (21). Previous studies have similarly reported the scar risk of KTP laser to be lower than lpNd:YAG laser (23). However, contrary to previous studies that reported no undesirable adverse effects such as purpura and crusting, we observed transient purpura accompanied with mild crusting in six patients on the side treated with Q-switched KTP (585 nm) laser, probably due to the higher wavelength of the laser mode.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…KTP laser has also been reported to be very safe when used in combination with topical retinaldehyde (21). Previous studies have similarly reported the scar risk of KTP laser to be lower than lpNd:YAG laser (23). However, contrary to previous studies that reported no undesirable adverse effects such as purpura and crusting, we observed transient purpura accompanied with mild crusting in six patients on the side treated with Q-switched KTP (585 nm) laser, probably due to the higher wavelength of the laser mode.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been reported that lpNd:YAG laser has advantages in the treatment of inflammatory lesions (2,7,14,15,23,24). In this study, the decrease in the number of pustules following lpNd:YAG laser treatment was remarkable.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Rhinophyma is a disfiguring disease of the nose characterized by sebaceous gland hypertrophy and proliferation of blood vessels and connective tissue. Phymatous changes are considered the end stage of acne rosacea and classically affect the lower 2/3 of the nose (rhinophyma), though involvement of the chin (gnathophyma), forehead (metophyma), or ear (otophyma) has also been described . The obvious cosmetic deformity and social stigmatization have motivated patients to seek curative treatments, with destructive methods preferred to medical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Rozasea için farklı tedavi seçenekleri vardır. Eritematelenjiektazik rozaseada 595 nm pulsed dye lazer (PDL) iyi bir seçenek olarak bildirilmektedir3 . Rozasea, yaşam kalitesini olumsuz yönde etkilemektedir.…”
unclassified